PENGARUH TEMAN SEBAYA TERHADAP PERILAKU MEROKOK PESERTA DIDIK KELAS VIII DI SMP KARTIKA I – 7 PADANG - Annisa Yusiana; Yasrial Chandra; Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Smoking behavior among adolescents remains a common problem in the school environment and is strongly influenced by social factors, particularly peer groups. This study aimed to describe the level of peer influence, describe the smoking behavior of students, and analyze the effect of peer influence on the smoking behavior of eighth-grade students at SMP KARTIKA I-7 Padang. This research employed a quantitative approach using a simple regression analysis design. The population consisted of 35 students identified as smokers, and the total sampling technique was applied so that all members of the population were selected as research participants. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that peer influence was categorized as high, while students' smoking behavior was categorized as moderately high. The results of the simple linear regression analysis indicated that peer influence had a significant effect on students' smoking behavior, contributing 45.1% to the variance in smoking behavior, while the remaining 54.9% was influenced by other factors outside the scope of this study. These findings indicate that stronger peer influence tends to increase the likelihood of smoking behavior among students. Therefore, school counselors and educational institutions are expected to strengthen preventive counseling services, group guidance activities, and smoking prevention programs by involving peer groups as positive agents of change.